The role of governing boards in improving patient experience: Attitudes and activities of health service boards in Victoria, Australia - Marie Bismark (The Beryl Institute, 2014)
The authors sought to determine the attitudes of public health service board members and senior executives toward patient experience and to describe the governance activities of the boards in this area. The study was based on an online survey of 322 board members from 85 public health services and semi-structured interviews with 35 board members and senior executives from 13 public health services in Victoria, Australia. The results showed that while some health service boards had high aspirations and clear plans for improving patient experience, others remained sluggish or even cynically resistant to changing their existing models of care. Interviewees associated with highly active boards described initiatives to improve patient experience at multiple levels in the organisation - from boardroom to bedside. Among less active boards, efforts to improve patient experience tended to be more ad hoc and there was greater uncertainty about how to scale up or systematise. The authors conclude that addressing the gap between the responsibility of boards to address patient experience, and the reality of their governance activities, requires a nuanced understanding of the attitudes and activities of board members. The approaches taken by “positive attitude, high activity” boards could be showcased as exemplars for others.